Experimental research and engineering application on the treatment of desulfurization wastewater from coal-fired power plants by spray evaporation. (April 2021) - Sun, Zongkang; Chen, Haijie; Zhao, Ning; Feng, Yongxin; Liu, Fengjun; Cai, Chenjian; Che, Guangmin; Yang, Linjun
Graphical abstract: Highlights: The desulfurization wastewater was treated by spray evaporation. Wastewater atomization and evaporation characteristics were studied systematically. The spray evaporation technology was applied in a 330 MW coal-fired power plant. It has good adaptability to different kinds of wastewater and working conditions. This system had little adverse effect on the flue gas and particle characteristics. Abstract: The spray evaporation is a promising zero discharge technology for desulphurization wastewater treatment. In this work, a pilot-scale platform for the spray evaporation of desulfurization wastewater was built, the desulphurization wastewater was atomized by a rotary atomizer and evaporate in the evaporation tower, and the wastewater atomization and evaporation characteristics were investigated systematically. The results showed that the increase of atomizer rotating speed can improve the atomization effect of desulfurization wastewater, while the increase of its flow rate and total amount of dissolved solids (TDS) was not conducive to that. For the evaporation of desulfurization wastewater, the increase of flue gas temperature, gas-liquid ratio (the ratio of flue gas volume to desulfurization wastewater volume, Nm 3 m −3 ) and atomizer rotating speed can promote its rapid evaporation, while the increase of wastewater TDS reduced the evaporation rate of wastewater droplets. On this basis, a bypass evaporation tower system was designed and constructed in a 330 MW coal-fired power plant to treat the desulphurization wastewater from limestone–gypsum wet flue gas desulfurization (WFGD) system, and the influence of wastewater evaporation on the flue gas and particle characteristics was investigated under different boiler loads. The results show that this evaporation system can ensure the evaporation effect of desulphurization wastewater under different boiler loads, lead to the reduction of flue gas temperature and the increase of humidity, reduce the concentration of SO2 and particles in flue gas, and enlarge the particle size at the outlet of evaporation tower. This work can provide a reference for the desulphurization wastewater treatment in coal-fired power plants.